Investigation on electrically conductive aggregates as grounding compound produced by Marconite - Mohd Tadza, Mohd Yuhyi; Tengku Anuar, Tengku Hafidatul Husna; Mat Yahaya, Fadzil (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Marconite is often used as alternative material to improve the performance of earth grounding system. This study aims to investigate of the physical and mechanical behaviour of conductive aggregate derived from Marconite namely, the electrical resistivity, water absorption, and crushing strength. In addition, similar tests were also conducted on mortar aggregate for comparison. The resistivity of aggregates were measured using soil box method.
Keywords: grounding system; conductive aggregate; Marconite; ground enhancement material; resistivity; grounding compound; system uziemienia; kruszywo przewodzące; materiał uszlachetniający; oporność; masa uziemiająca